A phosphate semiconductor-induced built-in electric field boosts electron enrichment for electrocatalytic hydrogen evolution in alkaline conditions. Issue 22 (24th May 2021) - Li, Zichuang; Pei, Yu; Ma, Ruguang; Wang, Yuandong; Zhu, Yufang; Yang, Minghui; Wang, Jiacheng
Abstract : A built-in electric field, by coupling n-type semiconductors with metallic clusters (Ru/BiPO4 ), makes electron-deficient BiPO4 favourable for H2 O-splitting and optimizes H adsorption on electron-rich Ru clusters, boosting the HER process. Abstract : At the semiconductor and metal interface, a built-in electric field leading to electron enrichment can be applied in developing efficient nano-hybrid catalysts because the induced electron-rich and electron-poor counterparts can synergistically modulate the active sites and elementary reaction steps. To overcome the extra difficulty in alkaline water dissociation during the production of green hydrogen, it is expected that such a built-in electric field can be constructed to boost interfacial electron enrichment to increase the water dissociation and hydrogen evolution kinetics. Herein, an n-type BiPO4 semiconductor is integrated with metallic Ru clusters (Ru/BiPO4 ) to produce an intrinsically built-in electric field, which causes electron enrichment via unidirectional electron transfer from BiPO4 to Ru. The resultant Ru/BiPO4 nanocomposite demonstrates superior water splitting activity toward electrocatalytic hydrogen evolution to Ru/C without electron enrichment in alkaline solution, and even exhibits nine-fold mass activity of commercial Pt/C in a harsher medium (3 M KOH). DFT calculation demonstrates that the positively charged BiPO4 matrix significantly decreases the energy barrier of water dissociation, while the negatively charged Ru clusters with more active electronic states optimize the proton adsorption and combination kinetics. The Ru layer in close contact with the phosphate matrix accepts the greatest number of electrons and shows the optimal Δ G H* . This work sheds new light on the advantage of the physical effect for designing advanced electrocatalysts for energy conversion and storage.